Analysis of physical exercises to improve physical abilities and shooting in young basketball players - Munadi , Mohammed J.; Jabbar, Zaid M.; Tuama, Hussein M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The science of athlete training and physiology has an important role in developing basketball athletes, especially for teenagers. Training causes many changes, whether it is physical or internal. The aim of this study was to prepare proposed exercises to develop some physical abilities, the functional variable and two-point jump shot in young basketball players, as well as to identify the effect of the proposed exercises on some physical abilities, the functional variable and two-point jump shot. The researcher used the experimental method. A total of 20 young basketball players of Nasiriyah Basketball Club were selected to participate in the study and were classified into experimental and control groups. Data were analyzed using T-test and Pearson’s correlation. The results showed that there were statistically significant differences (p<0.05) in the pre and post-tests for some physical and functional abilities and two-point jump shot in favor of the post-tests and in both groups (experimental and control). In conclusion, this study in young basketball players confirmed that continuing training by following the scientific methods and properly graduating the exercises placed in the main section of the training unit leads to achieve the desired goal when conducting the exercises consistently.